A new paradigm in facial reanimation for long-standing palsies? - Rajeev B. Ahuja; Pallab Chatterjee; Rajat Gupta; Prabhat Shrivastava; Gaurav K. Gupta (Indian Journal of Plastic Surgery)
Background: A chance observation of return of excellent facial movement, after 18 months following the first stage of cross-face nerve grafting, without free functional muscle transfer, in a case of long-standing facial palsy, lead the senior author (RBA) to further investigate clinically. Patients and Methods: This procedure, now christened as cross-face nerve extension and neurotization, was carried out in 12 patients of very long-standing facial palsy (mean 21 years) in years 1996-2011. The mean patient age and duration of palsy were 30.58 years and 21.08 years, respectively. In patients, 1-5 a single buccal or zygomatic branch served as a donor nerve, but subsequently, we used two donor nerves. The mean follow-up period was 20.75 months. Results: Successive patients had excellent to good return of facial expression with two fair results. Besides improved smile, patients could largely retain air in the mouth without any escape and had improved mastication. No complications were encountered except synkinesis in 1 patient. No additional surgical procedures were performed. Conclusion: There is experimental evidence to suggest that neurotization of a completely denervated muscle can occur by the formation of new ectopic motor end plates. Long-standing denervated muscle fibres eventually atrophy severely but are capable of re-innervation and regeneration, as validated by electron microscopic studies. In spite of several suggestions in the literature to clinically validate functional recovery by direct neurotization, the concept remains anecdotal. Our results substantiate this procedure, and it has the potential to simplify reanimation in longstanding facial palsy. Our work now needs validation by other investigators in the field of restoring facial animation.